(untitled) - Young, William M. Paul; (1955-...) (U.S.A, 2007)
Mackenzie Allen Phillips' youngest daughter, Missy, has been abducted during a family vacation and evidence that she may have been brutally murdered is found in an abandoned shack deep in the Oregon wilderness. Four years later in the midst of his Great Sadness, Mack receives a suspicious note, apparently from God, inviting him back to that shack for a weekend. Against his better judgment he arrives at the shack on a wintry afternoon and walks back into his darkest nightmare. What he finds there will change Mack's world forever. In a world where religion seems to grow increasingly irrelevant, `The Shack` wrestles with the timeless question, `Where is God in a world so filled with unspeakable pain?` The answers Mack gets will astound you and perhaps transform you as much as it did him.
Keywords: Life change events -- Fiction